Beaming effect for Fermi/LAT blazars. Issue Volume 10:Issue S313(2014) (24th March 2015) - Fan, J. H.; Xiao, H. B.; Bastieri, D.; Liu, Y.; Hao, J. M.; Pei, Z. Y.; Wu, D. X.; Yuan, Y. H.; Cai, W.; Lin, C.
Abstract: In this talk, we will show the beaming effect for Fermi/LAT blazars, then we discuss the correlations between γ-ray luminosity and other parameters, such as radio Doppler factors, superluminal motions, and core-dominance parameters. We also compare the Doppler factors determined from the γ-ray luminosity, X-ray emissions, and the short-term time scales with those from other methods. Our discussions suggest that γ-ray emissions may be strongly beamed.